3D Object detector: A multiscale region proposal network based on autonomous driving. (December 2022) - Chen, Xiu; Yang, Shuo; Li, Yingfei; Li, Yujie; Nakatoh, Yoshihisa
Abstract: Recently, 3D object detection by point cloud data processing has been applied to robotics and autonomous driving because of the popularity of the LiDAR sensors. Point cloud data contain the depth and geometric space information of an object as compared with the 2D images, and achieve high precision for classification and location. In the traditional processing of point cloud data, the disorder and sparsity of the points are significant problems. In addition, the traditional detector can only support processing a limited number of point clouds. Thus, it is difficult to detect objects using a large number of point clouds. However, the previous methods need to sample the point cloud data into a coarser type, so they cannot avoid the loss of information and the accuracy is affected, as seen in in PV-RCNN. In this paper, we propose a multiscale feature fusion detector called multiscale region proposal networks (MS-RPNs), which can provide multiscale prediction results for difficult category objects. Meanwhile, our method can improve the detection accuracy for smaller objects with the optimal processing of the multiscale feature extraction module. The efficiency and accuracy of the multiscale region proposal network on the KITTI 3D object detection datasets was evaluated using numerous experiments.